Effect of melatonin on stress-induced hyperglycemia and insulin resistance in critically-ill patients: A randomized double-blind, placebo-controlled clinical trial - Fahimeh Naderi-Behdani; Fatemeh Heydari; shahram Ala; Siavash Moradi; Saeid Abediankenari; Hosein Asgarirad; Elmira khodabakhsh (Babol University of Medical Sciences, 2022)
Background: Hyperglycemia is a common finding which is associated with increased mortality and morbidity among critically ill patients. There is currently no evidence that melatonin could improve stress induced hyperglycemia (SIH). In this study, we evaluated the effect of melatonin on blood sugar and insulin resistance (IR) in critically-ill patients. Methods: 104 critically-ill patients with SIH divided into two groups, receiving melatonin (6 mg BD for 3 days) or placebo. Changes of blood sugar, IR indices including homeostasis model assessment for insulin resistance and homeostasis model assessment adiponectin (HOMA-AD) ratios, Glasgow coma scale (GCS) were evaluated on the 4th day of melatonin prescription. On the 7Th day of study, changes of ventilator dependency and delirium were considered. Mortality and intensive care unit (ICU) stay were also compared between groups. Results: On day 4, patients in the melatonin group had significantly lower blood glucose and HMOA-IR level compared with the placebo group (P=0.04 and P=0.03, respectively) whereas HOMA-AD level did not differ significantly from placebo group (p>0.2). Also, we did not observe any significant difference in GCS level at this time between groups (p>0.2). On day 7, melatonin could not improve ventilator dependency and delirium significantly (p>0.2) and also could not reduce mortality and ICU stay in comparison with placebo (p>0.2, P=0.2, respectively). Conclusion: Melatonin supplementation showed positive effect on blood sugar and somehow insulin resistance whereas it could not improve ICU complications.